2005
DOI: 10.1097/01.mlg.0000157826.15756.67
|View full text |Cite
|
Sign up to set email alerts
|

A New Experimental Model of Acquired Cholesteatoma

Abstract: The presence of inflammatory cells may provoke the production of cytokines (IL-1, IL-2, IL-6, IL-8) and growth factors, which, together with the latex biomembrane, which is known to contain a protein that favors vascular growth, may cause chemotactic migration of the squamous epithelium from the external auditory meatus to the middle year of the rat, causing a cholesteatoma. The induction of an experimental cholesteatoma in rats with latex and latex plus 50% propylene glycol was effective, representing an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…[4] There are studies conducted on experimental animals, which have proven the theory of epithelial migration. [9] This had substantiated the claim of FB in the middle ear triggering the inflammatory reaction leading to cholesteatoma formation. This if not diagnosed early can cause serious intratemporal and intracranial complications.…”
Section: Discussionmentioning
confidence: 63%
“…[4] There are studies conducted on experimental animals, which have proven the theory of epithelial migration. [9] This had substantiated the claim of FB in the middle ear triggering the inflammatory reaction leading to cholesteatoma formation. This if not diagnosed early can cause serious intratemporal and intracranial complications.…”
Section: Discussionmentioning
confidence: 63%
“…Inflammation in the OCA occurs frequently in chronic OM, accounting for 88% of cases, 4 whereas the occurrence of cholesteatoma in the OCA is also common compared with other locations involving chronic OM in the middle ear. Experimental animal models have shown that perforation of the tympanic membrane in conjunction with a latex-induced inflammation in the middle ear can initiate the development of cholesteatoma, 5,6 suggesting that middle ear inflammation has an important role in the induction of cholesteatoma.…”
mentioning
confidence: 99%
“…Technically, many modeling methods have been reported to successfully induce cholesteatoma including the ligation of the external ear canal [5,16], blocking of the eustachian tube [17,18], injection of chemical or biological material into the middle ear [19], autologous dermal implantation [2,20,21], and local hybrid ear [6]. However, in the present study we implanted autologous meatal skin grafts into the middle ear via the tympanic membrane followed by an intratympanic injection of PA to experimentally induce middle ear cholesteatoma in a mouse model.…”
Section: Discussionmentioning
confidence: 99%